Rediscovering, reevaluating, and restoring Entiatqua: Identifying pre‐Anthropocene valleys in North Cascadia, USA. (29th June 2022) - Powers, Paul; Staab, Brian; Cluer, Brian; Thorne, Colin
Abstract: A maturing body of evidence suggests that anthropogenic impacts on river‐wetland corridors (RWCs) are greater and more widespread than previously recognized. Partly, this stems from the difficulty of differentiating between legacy anthropogenic impacts and channel evolution resulting from natural disturbances. Here, we apply the geomorphic grade line (GGL) relative elevation model (REM) method to reveal pre‐Anthropocene fluvial features for a 42‐km reach of Entiatqua (English translation—the Entiat River) in the North Cascade Mountains, USA. We began by long profiling the entire length of the river valley and defining distinct valley segments based on breaks in profile. Next, we developed models of the valley profile for each segment, known as GGLs, and used them to develop high‐resolution REMs by detrending LiDAR‐derived digital elevation models. We then used the GGL‐REMs to map relict fluvial features in the valley floor. Validating the GGL‐REMs using surficial geologic maps, 14 Cdated soil profiles, and the identifiable remnants of historic dams allows us to differentiate surfaces associated with the pre‐Anthropocene from those resulting from anthropogenic activities, including splash damming, channel straightening, large wood removal, and beaver extirpation. Our findings reveal 1–2.5 m of anthropogenically‐driven channel incision in unconfined and partially‐confined valley segments, wherein fluvial sediment balances transitioned from being net depositional to erosive, and later neutral, with river environments in these segments shifting from being complex, ecologically‐rich, RWCs to simpler, ecologically‐impoverished, single‐thread channels, like those found in confined valley segments. The adverse impacts of post‐Anthropocene fluvial responses on salmon habitats were likely profound and may help explain historical and ongoing declines in populations of listed species, including Chinook Salmon ( Oncorhynchus tshawytscha ) and Steelhead Trout ( Oncorhynchus mykiss ). Our study of Entiatqua, together with evidence from other western US rivers, demonstrates that the GGL‐REM approach can be used to re‐envisage pre‐Anthropocene fluvial process‐form domains including identifying valley segments wherein fluvial responses to human development have disconnected RWCs. Once the pre‐Anthropogenic conditions of rivers like Entiatqua have been recognized, the case for restoring lost RWCs to unlock their ecological potential becomes compelling.